Anthropogenic forcing intensified internally driven concurrent heatwaves in August 2022 across the Northern Hemisphere - Kangjie Ma; Hainan Gong; Lin Wang; Bo Liu; Yulan Li; Huanhuan Ran; Wen Chen (npj Climate and Atmospheric Science)
Abstract In August 2022, unprecedented and long-lasting extreme heatwaves attacked the Northern Hemisphere, with simultaneous record-breaking surface air temperature (SAT) in Eastern Europe (EE), Southern China (SC), and Western North America (WNA). However, the underlying physical mechanisms of these concurrent heatwaves, and the extent to which they are driven by anthropogenic forcing versus internal variability remain unclear. Our analysis using the HadGEM3-A-N216 large ensemble attribution model reveals that anthropogenic forcing is responsible for approximately 50% of the heatwaves in EE and SC, and over 80% in WNA. Furthermore, an internally-generated circumglobal atmospheric wave train is identified as a key circulation factor facilitating these simultaneous heatwaves. Observations and numerical simulations indicate that extreme warm sea surface temperature (SST) anomalies in the North Atlantic, North Pacific and Barents Sea, along with extreme cold SST anomalies in the tropical central Pacific, are critical in the formation and maintenance of this atmospheric teleconnection wave train. Under future high-emission scenarios, the influence of the internally-generated atmospheric teleconnection on concurrent heatwaves may be enhanced, particularly in WNA.